Factors influencing land use changes in urban areas: The case of land development projects in Ilemela municipal council - Marwa , Julius C. (Mzumbe University, 2024)
A Dissertation submitted in fulfillment of the requirements for the award of degree of Master of Science in Project Planning and Management of Mzumbe University